2019
DOI: 10.1038/s41416-019-0384-y
|View full text |Cite|
|
Sign up to set email alerts
|

Tumour-reactive T cell subsets in the microenvironment of ovarian cancer

Abstract: Background Solid malignancies are frequently infiltrated with T cells. The success of adoptive cell transfer (ACT) with expanded tumour-infiltrating lymphocytes (TILs) in melanoma warrants its testing in other cancer types. In this preclinical study, we investigated whether clinical-grade TILs could be manufactured from ovarian cancer (OC) tumour specimens. Methods Thirty-four tumour specimens were obtained from 33 individual patients with OC. TILs were analysed for phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 42 publications
3
50
0
Order By: Relevance
“…A recent study reported that TIL culture resulted in grafts with a high CD4-to-CD8 cell ratio. 47 In contrast, we and others have frequently seen the inverse situation, perhaps reflecting variations in the TIL production protocols, 44 such as the concentration of IL-2 used. 47 In ACT with TILs, IL-2 is used for the in vivo maintenance of the TIL graft activity.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A recent study reported that TIL culture resulted in grafts with a high CD4-to-CD8 cell ratio. 47 In contrast, we and others have frequently seen the inverse situation, perhaps reflecting variations in the TIL production protocols, 44 such as the concentration of IL-2 used. 47 In ACT with TILs, IL-2 is used for the in vivo maintenance of the TIL graft activity.…”
Section: Discussionmentioning
confidence: 85%
“…47 In contrast, we and others have frequently seen the inverse situation, perhaps reflecting variations in the TIL production protocols, 44 such as the concentration of IL-2 used. 47 In ACT with TILs, IL-2 is used for the in vivo maintenance of the TIL graft activity. 4 Thus, production of IL-2 by Ad5/3-E2F-D24-hTNFa-IRES-hIL2 may explain the increase of TIL-derived IFNg seen (figure 4).…”
Section: Discussionmentioning
confidence: 85%
“…In a pilot study, ACT with TILs of patients with metastatic ovarian cancer resulted in a slight decrease of tumour size (maximally 23%) in five of six patients, but the effect was transient [94]. One of the reasons of a relatively modest therapeutic effect might be a low frequency (3%) of tumour-reactive T cells in ex vivo expanded TIL cultures [95]. Functional characterisation of expanded TILs from renal cell carcinoma and gastrointestinal cancer (GI) also revealed lower frequency of tumour-specific T cells compared to melanoma [96,97].…”
Section: Selected Ex Vivo Expanded Tumour-reactive Tils Vs Unselectementioning
confidence: 95%
“…ovarian cancer with ACT completed at our center have shown that ACT in metastatic ovarian cancer is feasible, but clinical responses were transient 25,26 . A phase I/II study combining ACT with checkpoint inhibitors has just been finalized (Kverneland et al, manuscript in preparation).…”
mentioning
confidence: 99%